2021
DOI: 10.4314/jasem.v24i12.18
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants of travel motivation and behaviour of visitors in nature-based destinations in northern Nigeria

Abstract: This study aimed to assess socio-demographic determinants of travel motivation and behavior of visitors in nature-based destinations in Northern Nigeria. Structured questionnaire was administered to 575 respondents at Chad Basin National Park; CBNP (69), Gashaka Gumti National Park; GGNP (165) and Yankari Game Reserve; YGR (341). Data were analyzed descriptively and inferentially. Results revealed that majority of the respondents at CBNP were males (72.5%), majority of the respondents at GGNP were females (77.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The study results show that 69.2% of respondents surveyed in the HiP were employed, while 30.8% were unemployed, indicating that most respondents surveyed were working or had a job -assuming they had disposable income and thus could afford to travel. These results confirm findings from the previous studies (such as those of Allaberganov & Preko, 2022;Stylidis, 2022;Wambani, Ogunjinmi & Oladeji, 2020).…”
Section: Respondents' Profilesupporting
confidence: 93%
See 2 more Smart Citations
“…The study results show that 69.2% of respondents surveyed in the HiP were employed, while 30.8% were unemployed, indicating that most respondents surveyed were working or had a job -assuming they had disposable income and thus could afford to travel. These results confirm findings from the previous studies (such as those of Allaberganov & Preko, 2022;Stylidis, 2022;Wambani, Ogunjinmi & Oladeji, 2020).…”
Section: Respondents' Profilesupporting
confidence: 93%
“…Tourism researchers (for example Lewis & D'Alessandro, 2019;Wambani, Ogunjinmi & Oladeji, 2020) concluded that tourism participation is strongly related to age, which is a significant socio-demographic factor that indicates how destinations may proceed with marketing segmentation. According to Ma et al (2018), age has a favourable influence on tourists' desire for leisure and nature exploration.…”
Section: Age and Push Travel Motivationmentioning
confidence: 99%
See 1 more Smart Citation